Augusto Pontes: uma trajetória formadora no campo musical cearense - Barros, Francisco Michel Alves (2018)
The purpose of this research is to analyze the trajectory of Augusto Pontes in the musical field of Ceará, to broaden the reflection about the concept of formation through the concept of the intellectual habitus. This concept - intellectual habitus formative - imbues the theoretical body of Pierre Bourdieu with the concepts of habitus, field and capital and the methodological approach of Life Stories in Formation or Biographical Method from the reflection of Christine Delory-Momberger with a look on the relationship between the biographical and the educational. The sources were mainly narratives recorded in documentaries, interviews for the accomplishment of other researches with related themes and journalistic records referring to the trajectory of the investigated agent. The formative intellectual habitus constitutes a reference that mobilizes other agents around or from within and moves the field, acting in a decisive way on their roles and mobility. The research contributes to the reflection of the concepts of education / formation, curriculum / knowledge and teaching / practices in the musical field, amplifying and re-significating them, revealing pedagogical aspects in non-school spaces, but significantly formative.